Mikrosirkulasi Pada Resusitasi Cairan - Hotber Pasaribu (Jurnal Ilmu Kedokteran, 2018)
The aim of fluid therapy during hemodynamic resuscitation is to increase global blood flow and increase flow to the microcirculation and therby, and thus oxygen availability for cellular respiration. Effect of volume expansion on microvascular perfusion might not always be in coherence with its macrocirculatory. It should be stressed that the total amount of volume administered during fluid resuscitation is believed to be a major determinant of outcome in critically ill shock patients. The purpose of this review is to evaluate the boundaries of macrohemodynamic approach to fluid administration and the integrated with microcirculatory.